Eschatology Discourse in Putru Pasaji - Agung Inten Mayuni, Anak; Wayan Suka Yasa, I; Wayan Budi Utama, I (International Journal of Psychosocial Rehabilitation, 2020)
Putru Pasaji is one of the most popular Hindu literature texts because it is always being read during the death ritual ‘mamukur.’ The existence and its function as mantra discourse eventually made this discourse not easily understood by Hindu society. Through critical discourse analysis, van Dijk, which focuses its analysis on text dimension, social cognition, and social context, it was found that the dominant discourse in the Putru Pasaji text is the Hindu eschatology. This refers to the spirit journey after death; concepts of svarga, naraka, karmaphala, punarbhawa, and moksa. Those concepts are related to offerings to establish eschatology discourse in Putru Pasaji holistically and comprehensively.